Beszélgetések a pszichoanalízisről 1/5 Freud és Bécs
Psychoanalysis is seen as one of the most influential intellectual trends of the 20th century, which came into being in Vienna at the end of the nineteenth century. Psychoanalysis profoundly changed the prevailing concept of the human psyche and established a theoretical and practical basis for modern psychological treatment. Its intellectual and cultural spread is still significant. Psychoanalysis tried to find answers not only to the problems of the individual but to social and cultural questions as well. Although society cannot be laid on the psychoanalytic coach, psychoanalysts still attempted to interpret social changes by analytic concepts. They tried to explain primarily the psychology of fascism and oppressive systems. As it is for the benefit of the individual if he tries to clarify the blind spots of his past, modern society also has to face its supressed tragedies. Psychoanalysis restores the continuity of the individual life and in this respect, for example, the present day working-through of the revolution of 1956 against Stalinism in Hungary restores the continuity of the collective memory. While in Freud's age hysteria and other anxiety neuroses were typical, in present day culture we can find rather the self-loving, narcissistic personality and mess culture serving it. Among other things this is why psychoanalytic theory and practice has to be renewed to be able to meet these challenges. The criticizm concerning the scientific basis, the relativity of therapeutic truth and the effectiveness of treatment in psychoanalysis can promote this aim. In these conversations we concentrate on the relationship between psychoanalysis and present day society. Péter Forgács